Dual column approach for the purification of zinc finger proteins by immobilized metal affinity chromatography. (October 2018) - Ko, Ching-Chung; Ostermeier, Marc; Lin, Sung-Chyr
Graphical abstract: Highlights: Purification of zinc finger proteins by IMAC was demonstrated. Prior removal of metal ions from zinc finger increased adsorption capacity. A novel dual column process giving a purity of 98% was proposed. Purification under denaturing conditions was demonstrated. Abstract: The feasibility of using zinc fingers as the affinity tag for the purification of recombinant proteins with immobilized metal affinity chromatography (IMAC) was investigated. It was shown that upon the release of pre-existing metal ions from the model zinc-finger fusion protein by dialysis with buffer containing 500 mM NaCl, the recovery of the zinc-finger fusion protein was increased from 47% to 87%. The purity of the zinc-finger fusion protein was further improved with a pre-precipitation step at pH 5.0. The adsorption capacities for the zinc-finger fusion protein were in the order of Ni(II) > Cu(II) > Zn (II) > Co(II). Based on the low affinity of Zn(II)-loaded IMAC adsorbent for the model protein, a dual column process with Zn(II)-IMAC as the negative column for the removal of unwanted proteins and Ni(II)-IMAC as the positive column for the adsorption of the zinc-finger fusion protein was proposed, giving a purity of 98%. Purification of the zinc-finger fusion protein under denaturing conditions was also demonstrated. The results of this study suggest that it is possible to purify zinc finger proteins with IMAC without the need for external affinity tags, which is particularly useful for the purification of zinc finger proteins for structural analysis.